Comportamiento del mercado del cacao en Colombia, Ecuador y Perú del año 2007 al 2018 y sus futuros (2019)
The objective of this paper is to analyze the behavior of the cocoa market for Colombia, Ecuador and Peru from 2007 to 2018 and their futures, these countries are characterized by the production of cocoa in its different varieties, but are distinguished by fine cocoa with aroma, which is used to produce high quality fine chocolates. To achieve this objective, the work is developed under the methodology with a mixed approach in order to know the current state of the cocoa market in Colombia, Ecuador and Peru under the Grubel and Lloyd index, as well as to highlight the opportunities and challenges presented by these countries.